Differences in eating habits and physical activity before and during distance learning - Yulia Rizki Maulina; Ani Margawati; Rachma Purwanti; A. Fahmy Arif Tsani (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2022)
Background: The COVID-19 pandemic has led to the enforcement of distance learning. This may cause negative impacts on adolescents' eating habits and physical activity.Objectives: This study aimed to analyse the differences in eating habits and physical activity before and during distance learning in adolescents.Materials and Methods: A cross-sectional study was conducted on a sample of 95 adolescents aged between 15-18 years. Subjects were selected using a simple random sampling method. Eating habits and physical activity variables were measured using modified Eating Habit and Lifestyle Changes in COVID-19 and Eating Habits Questionnaire. Wilcoxon Signed-Rank and McNemar tests were used to analyse the data.Results: There was an increase in frequency of meals two times/day (9.5%) and snacking three times/day (4.2%) reported during distance learning. There were significant differences in number of meals (p=0.014) and snacking (p=0.034), carbohydrates sources intake (p=0.046), sweet food (p=0.014), snack (p=0.016), exercise (p=0.035), exercise duration (p=0.004), and exercise frequency (p=0.030) before and during distance learning. There were no significant differences in protein-sources intake, vegetable, fruit, sweetened beverages, fried food, processed food, junk food, emotional eating, physiological eating, and ways of obtaining food before and during distance learning (p >0.05).Conclusion: Significant differences were found in eating habits comprised of the number of main meals and snacking, intake of carbohydrates sources, sweet food, snack, and physical activity before and during distance learning